Monoene- and diene-type valepotriates from phyllactis pulvinata - Becker, Hans; Chavadej, Supa; Tauscher, Bernhard; De Abram, Ana Pastor; Finner, Emil; Borchers, Friedrich (Phytochemistry, 1986)
Four new valepotriates from Phyllactis pulvinata have been isolated, two are of the monoene type and two the diene type. In addition unknown valepotriates, presumably belonging to the IVHD-type, were detected in minor amounts. In relation to known valepotriates the new substances can be described as 1β-aceacevaltrate, 1-dehydroacevaltrate, 11α-acedidrovaltrate and 11α-acehomodidrovaltrate. The valepotriate content of the leaves was more than four times greater than that of rhizomes, mostly due to the monoene derivatives.